2020
DOI: 10.3390/su12083414
|View full text |Cite
|
Sign up to set email alerts
|

Assuming the Best: Individual Differences in Compensatory “Green” Beliefs Predict Susceptibility to the Negative Footprint Illusion

Abstract: Recent years have seen a marked increase in carbon emissions despite pledges made by the international community at the Paris Accord in 2015 to reduce fossil fuel production and consumption. Rebound effects could contribute to this phenomenon as, in which attempts to curb carbon emissions might have inadvertently led to an upswing in fossil fuel usage. The present study hypothesizes that rebound effects are driven by a misapplication of compensatory balancing heuristics, with the unintended outcome of producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 24 publications
1
33
4
3
Order By: Relevance
“…With respect to environment-specific thinking dispositions, the findings failed to reveal any effect of environmental concern ( Schultz, 2001 ) or the endorsement of compensatory green beliefs ( Kaklamanou et al, 2015 ) in explaining susceptibility to the negative footprint illusion. This lack of evidence is at odds with previous findings reported by MacCutcheon et al (2020) , which demonstrate a link between compensatory green beliefs and susceptibility to the negative footprint illusion. We note, however, that MacCutcheon et al (2020) demonstrated this significant association using a 9-point scale, rather than the 5-point scale adopted in the present study, which suggests that our replication failure might be attributable to a lack of sensitivity arising from a reduced range of scale.…”
Section: Studycontrasting
confidence: 92%
See 3 more Smart Citations
“…With respect to environment-specific thinking dispositions, the findings failed to reveal any effect of environmental concern ( Schultz, 2001 ) or the endorsement of compensatory green beliefs ( Kaklamanou et al, 2015 ) in explaining susceptibility to the negative footprint illusion. This lack of evidence is at odds with previous findings reported by MacCutcheon et al (2020) , which demonstrate a link between compensatory green beliefs and susceptibility to the negative footprint illusion. We note, however, that MacCutcheon et al (2020) demonstrated this significant association using a 9-point scale, rather than the 5-point scale adopted in the present study, which suggests that our replication failure might be attributable to a lack of sensitivity arising from a reduced range of scale.…”
Section: Studycontrasting
confidence: 92%
“…This lack of evidence is at odds with previous findings reported by MacCutcheon et al (2020) , which demonstrate a link between compensatory green beliefs and susceptibility to the negative footprint illusion. We note, however, that MacCutcheon et al (2020) demonstrated this significant association using a 9-point scale, rather than the 5-point scale adopted in the present study, which suggests that our replication failure might be attributable to a lack of sensitivity arising from a reduced range of scale.…”
Section: Studycontrasting
confidence: 92%
See 2 more Smart Citations
“…In terms of explanations for the negative footprint illusion, one study has proposed that compensatory green beliefs (e.g. "I recycle, therefore I can drive my car to work") are a key predictor of the illusion (MacCutcheon et al, 2020), and evidence gleaned from two other studies suggest that it is underpinned by an averaging bias (Holmgren et al, 2018a;Holmgren et al, 2019). More specifically, instead of considering each item's individual environmental impact and making an estimate based on the aggregated sum, people seem to make a vice/virtue categorisation of each item (e.g.…”
Section: Cognitive Biases In the Environmental Domainmentioning
confidence: 99%